PELATIHAN DASAR - DASAR WAKAF DI BUMI LANCANG KUNING PEKANBARU RIAU - Idel Waldelmi; Afvan Aquino; Wita Dwika Listihana; Aznuriyandi Aznuriyandi; Erma Wahyu Ningsih (Jurnal Pengabdian Kompetitif, 2025)
This Basic Training on Waqf in Bumi Lancang Kuning, Pekanbaru, Riau aims to assess the literacy (knowledge, understanding, and belief) of the community regarding waqf and to identify opportunities and challenges in its development in Pekanbaru, Riau, Indonesia. The results of the implementation and survey (pre-test and post-test) show that most respondents (more than 70%) have high confidence in the potential of waqf as a sustainable socio-economic instrument. However, a small number still express doubts due to low waqf literacy and trust in the managing institutions. Conceptually, waqf is an Islamic philanthropic instrument that has a special feature in that the assets donated as waqf are eternal and cannot be sold, gifted, or inherited. This principle makes waqf a source of long-term benefits for the community. The great opportunity for waqf development lies in the synergy between community literacy, innovation in productive waqf management, and government policy support. However, the challenges include public trust, the professionalism of managers, and continuous education. Therefore, collaborative efforts between educational institutions, the government, and nazhir are needed to strengthen public confidence and participation in order to create an effective and socially just waqf ecosystem.